Marine Microbial Diversity as Source of Bioactive Compounds - Shaaban, Khaled A. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Over 70% of the Earth's surface is covered by oceans and seas, which are massively complex and consist of diverse assemblages of life forms. Marine bacteria, fungi, and other microorganisms develop unique metabolic and physiological capabilities that enable them to survive in extreme habitats and to produce compounds that might not be produced by their terrestrial counterparts. In the last few decades, the systematic investigations of marine/marine-derived microorganisms as sources of novel biologically active agents has exponentially increased. This Special Issue will focus on aspects relating to new bioactive metabolites from marine microorganisms including the isolation, taxonomy, and/or dereplication of microorganisms and the corresponding isolation, structure elucidation, biosynthesis, and/or biological activities of the new compounds. Comprehensive topical review articles relating to marine metabolites will also be considered.